Reimplantation Bypass Using One Limb of a Double-Origin Posterior Inferior Cerebellar Artery for Treatment of a Ruptured Fusiform Aneurysm: Case Report. Issue 3 (26th February 2020) - Lang, Michael J; Catapano, Joshua S; Paisan, Gabriella M; Koester, Stefan W; Cole, Tyler S; Labib, Mohamed A; Zhou, James J; Fredrickson, Vance L; Frisoli, Fabio A; Lawton, Michael T
Abstract: BACKGROUND AND IMPORTANCE: Posterior inferior cerebellar artery (PICA) aneurysms are uncommon, and aneurysms associated with anatomical PICA variants are even rarer. Although often treated endovascularly, aneurysms associated with anatomical PICA variants may not be suitable for endovascular intervention because of the risk of compromise of brainstem perforators and may be more amenable to open techniques. This case report describes the successful treatment of an aneurysm associated with a double-origin PICA (DOPICA) by distally reimplanting one of the PICA limbs. CLINICAL PRESENTATION: A 78-yr-old man with a Hunt-Hess grade III, Fisher grade IV subarachnoid hemorrhage secondary to a ruptured distal right PICA aneurysm associated with a DOPICA was treated with PICA-PICA bypass and trapping of the aneurysm. This is the first reported case in the literature of successful bypass of a DOPICA-associated aneurysm. Radiographically, the bypass remained patent with successful obliteration of the aneurysm, and at discharge from the hospital, the patient had a Glasgow Coma Scale score of 15 and modified Rankin Scale score of 3. CONCLUSION: This case demonstrates a novel reimplantation bypass for a ruptured aneurysm that exploits this rare variant anatomy of a DOPICA.